Gonadal Transcriptome Analysis of Male and Female Olive Flounder (Paralichthys olivaceus). (6th July 2014) - Fan, Zhaofei; You, Feng; Wang, Lijuan; Weng, Shenda; Wu, Zhihao; Hu, Jinwei; Zou, Yuxia; Tan, Xungang; Zhang, Peijun
Abstract : Olive flounder ( Paralichthys olivaceus ) is an important commercially cultured marine flatfish in China, Korea, and Japan, of which female grows faster than male. In order to explore the molecular mechanism of flounder sex determination and development, we used RNA-seq technology to investigate transcriptomes of flounder gonads. This produced 22, 253, 217 and 19, 777, 841 qualified reads from ovary and testes, which were jointly assembled into 97, 233 contigs. Among them, 23, 223 contigs were mapped to known genes, of which 2, 193 were predicted to be differentially expressed in ovary and 887 in testes. According to annotation information, several sex-related biological pathways including ovarian steroidogenesis and estrogen signaling pathways were firstly found in flounder. The dimorphic expression of overall sex-related genes provides further insights into sex determination and gonadal development. Our study also provides an archive for further studies of molecular mechanism of fish sex determination.